Acinus-S′ Represses Retinoic Acid Receptor (RAR)-Regulated Gene Expression through Interaction with the B Domains of RARs - Vucetic, Zivjena (American Society for Microbiology (ASM), 2008)
The diverse biological actions of retinoic acid (RA) are mediated by RA receptors (RARs) and retinoid X receptors (RXRs). Modulation of transcription by RARs/RXRs is achieved through two activation functions, ligand-independent AF-1 and ligand-dependent AF-2, located in the A/B and E domains, respectively. While the coregulatory proteins that interact with the E domain are well studied, the A/B domain-interacting partners and their influence(s) on the function of RARs are poorly understood. Acinus-S′ is an ubiquitous nuclear protein that has been implicated in inducing apoptotic chromatin condensation and regulating mRNA processing. Our data demonstrate that Acinus-S′ can specifically repress ligand-independent and ligand-dependent expression of a DR5 RA response element(RARE)-dependent reporter gene and several endogenous RAR-regulated genes in a dose-dependent and gene-specific manner. Chromatin immunoprecipitation assays show that Acinus-S′ associates with RAREs within the promoters of endogenous genes independent of RA treatment. Furthermore, the C-terminal end of Acinus-S′ and the B domain of RARβ interact independently of ligand, and the C-terminal end of Acinus-S′ is sufficient for the repression of RAR-regulated gene expression. Finally, histone deacetylase activity only partially accounts for the repressive effect of Acinus-S′ on RAR-dependent gene expression. These findings identify Acinus-S′ as a novel RAR-interacting protein that regulates the expression of a subset of RAR-regulated genes through direct binding to the N-terminal B domains of RARs.